Urocortinergic system in the epididymis of the normal and cryptorchid dogs. Issue 7 (21st May 2019) - Squillacioti, Caterina; Pelagalli, Alessandra; De Luca, Adriana; Liguori, Giovanna; Ali, Sabrina; Mirabella, Nicola
Abstract: Cryptorchidism is associated with changes in the gonads and the spermatic duct system, which may cause infertility problems. Urocortin (UCN) is a corticotrophin‐releasing hormone (CRH)‐related peptide, which affects several functions of male genital organs. The aim of the present study was to investigate the expression of UCN and its receptors CRHR1 and CRHR2 using immunohistochemistry, western blotting and real‐time reverse transcription polymerase chain reaction in tissues collected from the epididymis of normal and cryptorchid dogs. The lumen of the cryptic epididymal duct was found to be relatively smaller than that of the normal one, and interstitial tissue was abundant in the cryptic epididymis. In addition, only a few spermatids were observed in the lumen of the epididymal duct. Results showed that UCN, CRHR2 and CRHR1 were expressed in tissues collected from normal and cryptic epididymal ducts. Urocortin‐ and CRHR2‐immunoreactivities (IRs) were detected in the principal cells of the caput, corpus and cauda of the normal and cryptic epididymides. CRHR1‐IR was detected in vascular smooth muscles and fibromuscular cells surrounding epididymal tubules of the normal and cryptorchid dogs. Expression levels of UCN and CRHR2 mRNA were higher in cryptic epididymal ducts than that in normal epididymal ducts. These results suggest that UCN and its receptors might play a role in regulating the maturation and storage of spermatozoa. These findings indicated that the expression of these proteins could be modulated by the cryptorchidism condition.